Aortic valve-sparing in aortic dissection with transposition of great arteries. (April 2013) - Sharma, Rajiv; Cohen, Brent; Peters, Paul; Shah, Pallav
Patients with transposition of the great arteries have good survival after surgery, but some have complications ranging from heart failure to valve dysfunction. A 42-year-old woman who underwent surgical correction in childhood, presented with aortic dissection and had a valve-sparing root operation, but died immediately postoperatively. Both aortic dissection and valve-sparing root operations in this setting have not been described before. This case highlights facts to consider in the treatment of this presentation.